Employment Choices of Persons with Disability (PWDs) in Metro Manila - Christian D. Mina (Philippine Institute for Development Studies (PIDS), 2010)
This paper examined how PWDs in the Philippines make a living and determined the factors that influenced them to select a particular labor market status and/or a source of personal income. It also analyzed the different types of work these PWDs engage in and their association with levels of education. Using dataset from the pioneering survey on socioeconomic conditions of PWDs in selected cities in Metro Manila, Philippines conducted in 2008, econometric analyses were conducted. The paper then presented some insights that could help the government craft better policy strategies in the provision of livelihood to, as well as empowerment of, PWDs.
Keywords: 330; Philippines; employment; labor force participation; multivariate adaptive regression splines; logistic regression; disability; occupation; source of income; principal component analysis; correspondence analysis; Behinderte Arbeitskräfte; Erwerbstätigkeit; Manila; Philippinen